Death - Kagan, Shelly (Open Yale courses series., 2012)
There is one thing we can be sure of: we are all going to die. But once we accept that fact, the questions begin. In this thought-provoking book, philosophy professor Shelly Kagan examines the myriad questions that arise when we confront the meaning of death.